Effect of the earth’s conductivity on the radiation characteristics of monopole antenna - Singh K.P.; Shukla P.K. (My University, 2025)
An expression for the electric and magnetic fields at a far point due to a monopole antenna on the conductive Earth is obtained. With the Earth's conductivity term included the radiated power and the radiation resistance of the monopole antenna have been calculated. The variation of radiation resistance with conductivity of the Earth and radiation frequency has been studied. © 1972, Taylor & Francis Group, LLC.